Impact of Pre-Transplantation Psychological Counseling in Improving the Mental Well-Being of Patients on Hemodialysis - Zhao, Qianyun; Zhang, Sen; Yu, Ran (Frontiers in Psychiatry, 2021)
Background: Patients who are on hemodialysis (HD) and are waiting for kidney transplantation encounter various psychological issues. Objective: The current research aimed to compare the effectiveness of regular nursing care with that of nursing care coupled with dedicated psychological counseling in patients who were on HD before they underwent kidney transplantation. Methods: Baseline data were collected 1 month before kidney transplantation in patients of both the control (patients who received general nursing care between August 2011 and June 2015) and intervention (patients who received nursing care and psychological counseling between June 2015 and July 2018) groups. The Mental Status Scale in Non-Psychiatric Settings (MSSNS) was administered to assess and record the psychological status. Clinicodemographic and end-stage renal disease (ESRD)-related details, including duration of dialysis, causes for ESRD, the number of dialysis sessions performed before transplantation, and MSSNS scores, were recorded and compared between the groups. Results: A total of 37 patients were enrolled, including 19 in the control group and 18 in the intervention group. The number of dialysis sessions performed before transplantation was 143 (26, 564) and 227.5 (39, 767), and dialysis duration was 20.4 ± 14.5 and 14.4 ± 12.1 months in the intervention and control groups, respectively. There was no significant difference in baseline negative emotions between the two groups (P > 0.05). The psychological intervention group reported significantly lower anxiety, depression, anger, and loneliness scores than the control group (P < 0.05). Conclusion: Psychological counseling before kidney transplantation in patients on HD could reduce their negative emotions and enhance mental well-being.